2012
DOI: 10.4102/sajr.v16i2.309
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound diagnosis of ulnar nerve dislocation and snapping triceps syndrome

Abstract: Dislocation of the ulnar nerve with snapping triceps syndrome has been implicated as a cause of cubital tunnel syndrome. Patients with this condition may clinically present with a snapping sensation at the elbow upon flexion along with ulnar neuropathic symptoms. Though demonstration of this condition is possible by static MRI images, ultrasound can be used as a more accessible and inexpensive modality for attaining diagnosis. This pictorial essay emphasises the technique, findings and role of dynamic ultrasou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…The isolated snapping ulnar nerve may be palpated. MRI in the flexion position can show that the ulnar nerve has come out of its groove (44). Dynamic ultrasound can reveal the snapping of the ulnar nerve during elbow movements (44).…”
Section: Extra-articular (Medial) Snappingmentioning
confidence: 99%
See 1 more Smart Citation
“…The isolated snapping ulnar nerve may be palpated. MRI in the flexion position can show that the ulnar nerve has come out of its groove (44). Dynamic ultrasound can reveal the snapping of the ulnar nerve during elbow movements (44).…”
Section: Extra-articular (Medial) Snappingmentioning
confidence: 99%
“…MRI in the flexion position can show that the ulnar nerve has come out of its groove (44). Dynamic ultrasound can reveal the snapping of the ulnar nerve during elbow movements (44). A recent study using dynamic ultrasound visualization identified a significant prevalence of ulnar nerve displacement in young baseball players, although some forms of nerve subluxation may also be observed in asymptomatic patients (45).…”
Section: Extra-articular (Medial) Snappingmentioning
confidence: 99%
“…25 The condition is also seen in bodybuilders, abnormal triceps tendons, and posttrauma. 26 Dislocation occurs if the nerve slides out of the cubital tunnel and over the medial epicondyle during elbow flexion. Ulnar nerve subluxation/dislocation can occur independently of a snapping distal triceps tendon.…”
Section: Snapping Triceps/ulnar Nerve Subluxationmentioning
confidence: 99%
“…22 The ulnar nerve also flattens during flexion in patients with subluxation. 26 This may be accompanied by abnormal anterior translation of the medial head of the triceps muscle ( Figure 4C and D). Longitudinal dynamic imaging during flexion and extension is useful to differentiate partial from nonretracted complete distal triceps tendon tears.…”
Section: Snapping Triceps/ulnar Nerve Subluxationmentioning
confidence: 99%